Designing culture : behavioral strategy for the workplace - Woolsey, Kristi, author (O'Reilly Media, 2016)
In today’s highly competitive landscape, humans are not just cogs in a machine. They are the machine itself. If you want to outstrip your competitors, you need to influence not only how people work, but also how they work together. This O’Reilly report examines how your organization can use behavioral science to design a workplace culture that supports creativity, collaboration, and innovation among your employees. Author Kristi Woolsey walks you through a behavioral strategy framework that can help you increase productivity and improve employee attraction and retention. With detailed case studies of a biomedical engineering company, a university, and a skincare product manufacturer, this report shows you that creating culture affects several areas, including: Organizational structure: hierarchies, teams, and team size Programs and amenities: everything from free food to compensation strategies and recurring meetings Digital and mechanical tools and systems that support your work processes Digital and physical space where your employees work, connect, and collaborate Pick up this report and learn how organizations can measure in dollars the positive results of an environment designed to influence workplace behavior. About the author Kristine Woolsey is the practice lead for creative environments at MAYA, a design and technology innovation consultancy. Kristi is well known as a behavioral strategist with years of speaking and research on the impact that the physical environment has on human behavior. She also founded Woolsey Studio, which by 2000 was the largest West Coast women-led architecture firm.